Effect of COVID-19 restriction measures on multidrug resistant tuberculosis case notifications and treatment outcomes at treatment centres in Uganda - Pamela Okwir Apio; Lydia Nakiyingi; Charles Batte; Pius Mukisa; John Mukisa; Monica Okwir Acen; Andrew Weil Semulimi; Achilles Katamba; Joan Nakayaga Kalyango (BMC Infectious Diseases)
Abstract Background Multidrug resistant tuberculosis (MDR-TB) is a global public health threat. In 2021, an incidence of 3.6% was reported among new TB patients, and 18% was reported among previously treated patients. The emergence of the COVID-19 pandemic impacted the health sector, although little is known about the effect of restrictive COVID-19 measures on MDR-TB case notifications and treatment outcomes in Uganda. This study aimed to assess the effect of COVID-19 restriction measures on MDR-TB case notifications and treatment outcomes at treatment centres in Uganda. Methods This was a retrospective cohort study in which a total of 483 participants were enrolled—238 before (March 2018-February 2020) and 245 during (March 2020-February 2022) COVID-19 restrictions. The data were extracted from the Drug-Resistant Tuberculosis (DR-TB) Health Management Information System (HMIS), and patient charts, and census sampling was employed. Interrupted time series (ITSA) was used to compare MDR-TB case notifications and treatment outcomes. Results Before the COVID-19 restrictions, the majority 58.0% were aged less than or equal to 38 years whereas during the restrictions, the majority 51.8% were aged greater than 38 years. A total of 238 cases of MDRTB were reported before, and 245 cases were reported during the restrictions. There was no immediate (β2; 0.134) or sustained (β3; 0.494) impact of COVID-19 restriction measures on monthly MDR-TB case notifications. The mean number of monthly MDR-TB notifications was similar for the 3-month period before (11.0 cases per month) and during (10.0 cases per month) the COVID-19 restrictions (p-value 0.661). The proportions of patients who achieved successful MDR-TB treatment before (81.5%) and during (81.7%) COVID-19 restriction was not significantly different (p- value < 0.001). During the COVID-19 restrictions, not being married (aPR 0.85, 95% CI: 0.74—0.97) and treatment delay greater than 7 days (aPR 0.87, 95% CI 0.78—0.96) were negatively associated with successful treatment outcomes. Conclusion Restrictive COVID-19 measures did not affect MDR-TB case notifications or treatment outcomes. Not being married and having a treatment delay greater than 7 days reduced the chances of a successful treatment outcome during COVID-19. The WHO and MoH should continue strengthening active case finding, contact screening and community engagement to consolidate MDR-TB control and management in preparation for similar future pandemics.